Dislocations. Issue 9 (25th August 2020) - Fernández‐Sánchez, Javier; Ott, Dennis
Abstract: Dislocation is a kind of construction in which a phrasal constituent (the dislocate) appears at the outer left or right edge of a gap‐less clause (its host) that contains a pronominal correlate of the dislocate. Dislocations are widely attested and presumably universally available across languages. The construction raises a number of problems for core assumptions of syntactic theory, in that these assumptions appear to thwart any coherent resolution of the question of how the dislocate relates to the internal structure of its host. This contribution is divided into two parts. In Part 1, we review central empirical properties of dislocation, which, taken together, appear to defy the laws of syntax as commonly assumed. In Part 2, we review key proposals that have emerged over the last decennia to resolve this paradox and restore dislocations to normalcy.